2016
DOI: 10.1016/j.exger.2016.03.001
|View full text |Cite
|
Sign up to set email alerts
|

No Association between Variation in Longevity Candidate Genes and Aging-related Phenotypes in Oldest-old Danes

Abstract: In this study we explored the association between aging-related phenotypes previously reported to predict survival in old age and variation in 77 genes from the DNA repair pathway, 32 genes from the growth hormone 1/insulin-like growth factor 1/insulin (GH/IGF-1/INS) signalling pathway and 16 additional genes repeatedly considered as candidates for human longevity: APOE, APOA4, APOC3, ACE, CETP, HFE, IL6, IL6R, MTHFR, TGFB1, SIRTs 1, 3, 6; and HSPAs 1A, 1L, 14. Altogether, 1,049 single nucleotide polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…While this approach may eventually fulfill its promise, hypothesis-driven tests of longevity linked gene variants have generally failed to replicate [4546]. For example, a large and careful retest of three aged Danish cohorts came up empty-handed after surveying variants in 125 well known genes implicated in aging based on known molecular functions [47]. The conventional excuse for failures of this type is that longevity is a complex, multifactorial phenotype influenced by small contributions from many DNA variants (and of course, many environmental factors), making any one sequence variant exceedingly difficult to validate using simple association studies of this type [4849].…”
Section: Introductionmentioning
confidence: 99%
“…While this approach may eventually fulfill its promise, hypothesis-driven tests of longevity linked gene variants have generally failed to replicate [4546]. For example, a large and careful retest of three aged Danish cohorts came up empty-handed after surveying variants in 125 well known genes implicated in aging based on known molecular functions [47]. The conventional excuse for failures of this type is that longevity is a complex, multifactorial phenotype influenced by small contributions from many DNA variants (and of course, many environmental factors), making any one sequence variant exceedingly difficult to validate using simple association studies of this type [4849].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of the relation between SRH and APOE reported no association in oldest-old Danes ( 51 ), while an association was found in Taiwanese individuals aged 54–91 ( 52 ). The SNP rs2075650 in TOMM40 was not included in any of these studies.…”
Section: Discussionmentioning
confidence: 89%
“…IGF-1, in contrast to adiponectin, IL-6 and cystatin-C, was not found to correlate with several functional declines indices ( n = 3372, 73 ± 6 years old, 7 years follow-up) [ 131 ], but subjects within the lowest quartile of IGF-1 ( n = 4133, 72 ± 6 years old) were more likely to exhibit pre-frailty or frailty [ 132 ]. On the other hand, population studies exploring single nucleotide polymorphisms (SNPs) involved in GH signalling were not able to detect relationships with physical or cognitive performance in two large cohorts of almost centenarian Danes [ 133 ], while animal models of GH deficiency exhibit remarkable longevity, reduced cell senescence and improved metabolic profile [ 134 ]. Therefore, there is also a possibility that the weakening of somatotropic axis in humans could bear protection over chronic conditions.…”
Section: To Grow or Not To Grow Till Late Age?mentioning
confidence: 99%